DEVELOPMENT OF A LOW-COST IOT-BASED FRAMEWORK FOR REAL-TIME MONITORING OF RENEWABLE ENERGY SYSTEMS IN RURAL ANAMBRA STATE, NIGERIA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2026)
Introducing renewable energy systems, especially solar plants in the rural communities of the developing world like Nigeria have played a critical role in relieving the energy poverty but problems like inefficient systems, expensive maintenance, and real-time monitoring have still remained a challenge. This research forms and executes a low-cost Internet of Things (IoT) system to track renewable energy infrastructure in rural in underserved Anambra State, Nigeria, and specifically solar photovoltaic (PV) systems. The first goal is to create a community-based and scalable solution, which improves reliability and efficiency due to the ability to detect faults, track performance, and create maintenance-based on the data. The study will use a mixed-method design in sample of 50 households in Awka South and Anaocha Local Government Areas, which have been identified through purposive sampling to reflect the normal energy user in villages. Scheduling Data are to be collected through baseline surveys with structured questionnaires, prototype development with the help of Arduino microcontrollers, sensors, and GSM modules, and pilot implementation over a month and in 10 households. The quantitative analysis will involve descriptive statistics, paired t-tests to determine the efficiency at the beginning and the end of the implementation and the thematic analysis will evaluate the qualitative assessment of the usability through qualitative feedback. According to the results, the energy output has increased by 25% and the downtime decreased by 40% and the participants have expressed high satisfaction rates because of saving costs and convenience. The sample is composed of Igbo households, the majority of which are of an average age at 45 years, with low levels of literacy (60 percent- primary education) and dependent on agriculture. This system deals with distinct limitations such as unpredictable rainfalls and excessive sunlight in Anambra, which facilitates the use of renewable energy. The paper has something new to the knowledge of computer engineering, because they have shown cheap IoT applications where resources are limited, promoting energy equity and resilience.